1995
DOI: 10.1093/nar/23.10.1679
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Saccharomyces cerevisiae DNA repair gene RAD16

Abstract: The RAD16 gene product has been shown to be essential for the repair of the silenced mating type loci [Bang et al. (1992)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The targets of the checkpoint that are responsible for this effect are not yet known, but potential candidates include the NER factors Rad2, Rad7, Rad16, and Rad23 (6,25,31,46). In contrast, the checkpoint appears to function in TC-NER primarily via modification of repair factors, since inhibition of new protein synthesis via cycloheximide treatment had little or no effect on this repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The targets of the checkpoint that are responsible for this effect are not yet known, but potential candidates include the NER factors Rad2, Rad7, Rad16, and Rad23 (6,25,31,46). In contrast, the checkpoint appears to function in TC-NER primarily via modification of repair factors, since inhibition of new protein synthesis via cycloheximide treatment had little or no effect on this repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion mutants for these strains show an intermediate sensitivity to UV light and the gene products are thought to play an accessory role in NER (Prakash et al,1993). A number of studies show that the phenotypes of rad7 and rad16 mutants are almost indistinguishable, one of the few differences being the RAD16 gene's induction in response to heat shock (Bang et al, 1995). Terleth et al (1990) showed that both RAD7 and RAD16 were required for the repair of CPDs from the transcriptionally inactive HMLa locus.…”
Section: Discussionmentioning
confidence: 99%
“…There is no homology between the RAD7 (565 codons) and RAD23 (398 codons) at the amino acid sequence level, however. Like the RAD2 gene, which is indispensable for NER, the RAD7, RAD16, and RAD23 genes (but not other RAD genes required for NER) are transcriptionally up-regulated when cells are exposed to UV radiation (1,12,13,23).The partial UV radiation-sensitive phenotype of rad7 and rad16 mutants may relate to the observation that these genes are uniquely required for NER in certain transcriptionally repressed regions of DNA. Both rad16 (2) and rad7 (28,36) mutants are defective in the excision of pyrimidine dimers from the transcriptionally silent HML␣ and HMRa matingtype locus, yet they support efficient repair of the transcriptionally active MAT␣ locus.…”
mentioning
confidence: 99%
“…There is no homology between the RAD7 (565 codons) and RAD23 (398 codons) at the amino acid sequence level, however. Like the RAD2 gene, which is indispensable for NER, the RAD7, RAD16, and RAD23 genes (but not other RAD genes required for NER) are transcriptionally up-regulated when cells are exposed to UV radiation (1,12,13,23).…”
mentioning
confidence: 99%